Short-Term Relief with Upadacitinib: A Case Report of Palmoplantar Pustulosis in a Pediatric Patient - Gu Q; Zhang C; Lin Z; Fu Y; Li C; Ying Z (Clinical, Cosmetic and Investigational Dermatology)
Qinchen Gu,1,2 Chen Zhang,3 Zhimin Lin,4 Yiting Fu,5 Chen Li,6,7 Zhenhua Ying2,8,9 1The Second School of Clinical Medicine, Zhejiang Chinese Medical University, Zhejiang, 310014, People’s Republic of China; 2Department of Rheumatology and Immunology, Center for General Practice Medicine, Zhejiang Provincial People’s Hospital (Affiliated People’s Hospital, Hangzhou Medical College), Zhejiang, 310014, People’s Republic of China; 3Department of Rheumatology, Dongfang Hospital Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 4Third Affiliated Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 5Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 6Department of Dermatology, Tianjin Institute of Integrative Dermatology, Tianjin Academy of Traditional Chinese Medicine Affiliated Hospital, Tianjin, People’s Republic of China; 7Department of Rheumatology, Fangshan Hospital, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 8Institute of Rheumatology and Immunology, Hangzhou Medical College, Zhejiang, 310014, People’s Republic of China; 9Zhejiang Provincial Key Laboratory of Traditional Chinese Medicine Cultivation for Arthritis Diagnosis and Treatment, Zhejiang, 310014, People’s Republic of ChinaCorrespondence: Zhenhua Ying, Email yingzh2021@163.com Chen Li, Email casio1981@163.comAbstract: Palmoplantar pustulosis (PPP) is a chronic inflammatory skin disease with recurrent erythema, scales, and sterile pustules on the palms and soles. Treating PPP in children is difficult due to limited effective therapies, especially as there’s a lack of data on upadacitinib use in children under 12.This article reports a pediatric PPP case. The patient had severe, recurring rashes that affected daily activities. Treated with upadacitinib for two months, she showed a significant therapeutic response.Keywords: palmoplantar pustulosis, children, treatment, upadacitinib